1993
DOI: 10.1111/j.1751-1097.1993.tb04974.x
|View full text |Cite
|
Sign up to set email alerts
|

8‐METHOXYPSORALEN PLUS UVA INDUCES THE 72 kDa HEAT SHOCK PROTEIN IN ORGAN‐CULTURED NORMAL HUMAN SKIN

Abstract: The proteins induced by heat and other stressors, called heat shock proteins (HSP) or stress proteins, are considered to play a general role in protection from cellular injury. Exposure to UVA (320-400 nm) following application of 8-methoxypsoralen (8-MOP), termed PUVA is commonly used in the field of dermatology. In order to understand the induction of HSP in PUVA-treated human skin, indirect immunofluorescence using a monoclonal antibody specific for the 72 kDa HSP (HSP 72) was carried out in organ-cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…However, Trautinger et al 24 indicated that human keratinocytes constitutively express significant amounts of Hsp70. They 24 explained this discrepancy may be due to different techniques, in particular to a higher sensitivity of their three-step immunochemical techniques, as compared to the indirect immunofluorescence of Muramatsu et al 7,27 . These different results raise the question as to whether UV exposure induces expression of HSP70 in normal human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Trautinger et al 24 indicated that human keratinocytes constitutively express significant amounts of Hsp70. They 24 explained this discrepancy may be due to different techniques, in particular to a higher sensitivity of their three-step immunochemical techniques, as compared to the indirect immunofluorescence of Muramatsu et al 7,27 . These different results raise the question as to whether UV exposure induces expression of HSP70 in normal human keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Hsp70 may be further induced in epidermal keratinocytes by heat treatment, providing a state of resistance against the deleterious effects of heat 16 . UV-induced HSP70 expression was first reported by Muramatsu et al 7,27 in normal human skin system by an immunofluorescence method; Hsp70 expression was not detected at baseline 7,27 . However, Trautinger et al 24 indicated that human keratinocytes constitutively express significant amounts of Hsp70.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An accumulation of Hsp72 is induced not only by heat, but also by inducers of DNA damage in cultured human cells (Muramatsu et al, 1992(Muramatsu et al, , 1993(Muramatsu et al, , 1996Matsumoto et al, 1995). It was reported that HSP gene expression was depressed in rat muscle after experiencing spaceflight, and this was associated with a reduction in mechanical and neural activity levels (Ishihara et al, 2008).…”
Section: Msh2mentioning
confidence: 98%